1971
DOI: 10.1159/000155349
|View full text |Cite
|
Sign up to set email alerts
|

Rank Order in a Captive Female Squirrel Monkey Colony

Abstract: To determine if a rank order (RO) would be established among a group of 5 female squirrel monkeys, 14 behaviors were observed and performance in water dominance tests was recorded. Significant positive RO correlations were found between active contact and chasing, and between urine-washing and closed genital display. Significant negative RO correlations were found between active contact and huddling, and between chasing and huddling. The RO determined from the results of the water dominance tests was unstable.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1973
1973
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In his review article on primate status hierarchies, Bernstein [1970] cited several examples in which dominance hierarchy was determined from the direction of agonistic encounters. It is these dyadic interactions, not reported by Castell and Heinrich [1971], that provide the clearest evidence for dominance roles.…”
Section: Dominance Hierarchymentioning
confidence: 80%
“…In his review article on primate status hierarchies, Bernstein [1970] cited several examples in which dominance hierarchy was determined from the direction of agonistic encounters. It is these dyadic interactions, not reported by Castell and Heinrich [1971], that provide the clearest evidence for dominance roles.…”
Section: Dominance Hierarchymentioning
confidence: 80%
“…Squirrel mon keys in Corcovado are most exposed to heat stress during the dry season (January-March 1984), when daily hours of sunshine and maxi mum temperatures are greatest [52] and fol iage cover is minimal [32], During the dry sea son, however, troop members performed urine washing infrequently, less than 0.3% of sample time (about once per hour), the second lowest seasonal rate recorded. Data are sparse concerning the possible function of urine washing as an indictor of male dominance [21] or as a signal of arousal [23], At Corcovado the association between urine washing and social or affective contexts was weak. Unlike vocalizations, visual signals that are not directed towards an individual in close proximity are probably not reliably re ceived by these arboreal monkeys.…”
Section: Evaluation O F Hypothesized Functionsmentioning
confidence: 99%
“…Yet discussions concerning the function of urine washing have been inconclu sive. Suggested functions include: (1) marking trails for other members to follow [18]; (2) self-cleaning [20]; (3) displays of dominance [21,22] or mild arousal [23]; (4) enhanced grasping of branches during locomotion [24], and (5) facilitating thermoregulation by means of evaporative cooling [9,24]. Other behaviors that may be involved in scent depo sition for olfactory communication among troop members in squirrel monkeys include: (1) rump rubbing by females to promote male olfactory investigation [ 18] and (2) back rub bing by males, either to deposit scents or to acquire scents applied by conspecifics [18]; (3) chest rubs, postulated to spread the exu date of the sternal gland [ 19], and (4) sneezes, including nasal rubs on substrates and sneezes into the hand, which were initially suggested to disperse secretions of potential communi cative significance [25].…”
Section: Introductionmentioning
confidence: 99%
“…289-298). Castell and Heinrich (1971) and Talmage-Riggs and Anschel (1973) have shown that the occurrence of the urine wash is correlated positively with dominance: the higher the rank of the animal, the more urine washes are observed. Talmage-Riggs and Anschel (1973) suggest that the correlation may be due to the possible increased frequency of eating and drinking in dominant animals.…”
Section: Chemical Communicanon In Saimiri 469mentioning
confidence: 99%
“…Schmidt and Seitz (cited in Epple, 1974b) interpreted the urine wash in Saimiri as serving a thermoregulatory function, while Castell and Maurus (1967) suggested that its function was to keep the hands and feet clean and moist. Both Castell and Heinrich (1971) and Latta, Hopf', and Ploog (1967) have suggested that there are olfactory cues present in the urine that communicate the reproductive condition of the female. Thorington (1968, p. 80), to the contrary, concluded that there was no olfactory or other significance to the urine wash-at least among free-ranging animals.…”
mentioning
confidence: 99%